Medical complications of an aquatic innovation. Issue 13 (26th October 2009) - Mountjoy, M; Gordon, I; McKeown, J; Constantini, N
Abstract : The sport of swimming has been affected by the innovations of technology with the evolution of the swimsuit. The health benefits of swimming are numerous and are well documented in the scientific literature. As swimming is a low-impact sport, injuries are relatively uncommon. As a direct result of the new swimsuits, team physicians have identified the emergence of a new trend in injury in the aquatic athlete. Extensive blistering and ulceration of the finger tips and distal interphalangeal joints in addition to ecchymoses of the lower limb are now common in the aquatic athlete wearing the new swimsuits. Team physicians working with elite swimmers should be aware of this phenomenon and institute preventive measures.